Motivational Feature “Action” in Dialectal Names of Utensils in Yakut Language - E. R. Nikolaev (Научный диалог, 2023)
The main goal of the study is to describe verb roots in dialectal names of dishes in the Yakut language in order to identify motivational features semantically related to the category of ‘action’. The article employs a descriptive method using morphological and semantic analysis of words. The material for the study consists of lexical units extracted from dialectological and explanatory dictionaries, as well as field materials collected by the author. It has been established that the motivational feature of a derived word is determined by the meaning of the base word. The relationship between the meaning of the derived word and the verb root of the base word is clarified through the use of word-forming affixes that denote properties and functions of dishes: size and volume; cooking process (dishes). The main motivational feature in the examined names is ‘action’, including fermentation, collection, movement, flipping, scooping, etc. The base words include verbs such as ‘bas-’ (to scoop (water)), ‘khalbıy-’ (to remove (e.g., cream)), ‘homuy-’ (to gather), ‘köyör-’ (to wander (about kumis)), ‘khotor-’ (to extract (meat)), ‘tas-’ (to move (kumis)), 'daibaa-’ (to swing, in the sense of ‘scooping with a ladle’), ‘tier-’ (to flip). The author concludes that the realization of this motivational feature can be referred to as ‘verb-type motivation’.